The Correlation of the Average Increase in Blood Magnesium Levels with the Incidence of Preeclampsia After Magnesium Supplementation in Hypomagnesemic Pregnant Women at the Padang City Health Center - Utama, Try Genta; Djanas, Dovy (Andalas Obstetrics And Gynecology Journal, 2021)
Preeclampsia is a hypertensive disorder in pregnancy that occurs in 5-10% of pregnancies and occurs after 20 weeks of gestation and recovers spontaneously after delivery. Several studies have stated that one of the risks of hypertension in pregnancy is related to magnesium homeostasis. Magnesium plays an important role in forming new tissues (maternal and fetal). Pregnant women need a higher intake of magnesium than non-pregnant women of the same age. Magnesium deficiency during pregnancy not only causes problems for the nutrition of pregnant women and fetuses, but also associated with the occurrence of preeclampsia, preterm labor and muscle cramps during pregnancy. This study aims to determine the relationship between the average increase in blood magnesium levels with the incidence of preeclampsia in hypomagnesemic pregnant women.Keywords: preeclampsia, hypertension, blood magnesium levels